Preoperative Quality of Life in Patients with Small Vestibular Schwannomas - Matthias Scheich; Lisa Schultes; Manuel Stöth; Jens-Holger Krannich; Rudolf Hagen; Stephan Hackenberg; Miriam Bürklein (Journal of International Advanced Otology)
Background: Vestibular schwannomas (VS) are benign tumors arising from the eighth cranial nerve. They often cause no symptoms for a long period of time. Due to the improved availability and quality of magnetic resonance imaging diagnostics, even small tumors can be diagnosed at an early stage. The fact that the diagnosis of a VS might negatively affect a patient’s quality of life (QoL) should be taken into consideration when informing patients about various treatment options. However, little is known about the level of QoL in patients with small VS prior to scheduled surgery.